2020
DOI: 10.1515/pp-2020-0139
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of morbidity and mortality in patients submitted to cytoreductive surgery plus hyperthermic intraperitoneal chemotherapy for ovarian carcinomatosis: a multicenter study

Abstract: Objectives The aim of this retrospective study is to assess the incidence of morbidity and mortality related to cytoreductive surgery (CRS) plus hyperthermic intraperitoneal chemotherapy (HIPEC) and to evaluate their predictors, in patients with peritoneal metastasis of ovarian origin. Methods A retrospective multicenter study was carried out investigating results from eight Italian institutions. A total of 276 patients met i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…transfusion requirement as independent predictors of major complications following CRS/HIPEC. 18,19 Data previously published from Waikato Hospital found significantly fewer blood transfusions than another Australian cohort, likely due to surgical haemostasis and judicious blood product use. 17 The effect of operative duration on major complication rate likely reflects both technical proficiency and pre-operative case selection.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…transfusion requirement as independent predictors of major complications following CRS/HIPEC. 18,19 Data previously published from Waikato Hospital found significantly fewer blood transfusions than another Australian cohort, likely due to surgical haemostasis and judicious blood product use. 17 The effect of operative duration on major complication rate likely reflects both technical proficiency and pre-operative case selection.…”
Section: Discussionmentioning
confidence: 94%
“…Operative duration was an independent risk factor for major complications. Previous studies have identified PCI, blood loss, and transfusion requirement as independent predictors of major complications following CRS/HIPEC 18,19 . Data previously published from Waikato Hospital found significantly fewer blood transfusions than another Australian cohort, likely due to surgical haemostasis and judicious blood product use 17 .…”
Section: Discussionmentioning
confidence: 97%
“…Macrì et al recorded the ECOG score and severe morbidity as predictors of 60-days survival [ 152 , 153 ].…”
Section: Treatment Of Ovarian Cancer Metastatic Peritoneal Surface Ma...mentioning
confidence: 99%